2015
DOI: 10.1371/journal.pone.0122924
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Peripheral Mu-Opioid Receptor Mediated Analgesia in Rat Orofacial Persistent Pain Model

Abstract: Unilateral ligation of the tendon of anterior superficial part of rat masseter muscle (TASM) leads to long-lasting allodynia. Sex differences in peripheral mu-opioid receptor (MOR)-mediated analgesia under persistent myogenic pain are not well understood. In this study, we examined (1) whether locally applied MOR agonists attenuate persistent pain following TASM ligation in a sex dependent manner, (2) whether there are sex differences of MOR expression changes in rat trigeminal ganglia (TG). The effects of MOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…Indeed, using a variety of acute and chronic pain assays, researchers have shown that morphine’s median effective dose in female rodents is approximately twice the concentration of the dose needed for males to achieve comparable levels of pain relief (Kepler et al, 1989; Cicero et al, 2002; Ji et al, 2006; Loyd and Murphy, 2006; Loyd et al, 2008; Posillico et al, 2015). Researchers using other opioids have reported similar results (Barrett et al, 2002; Bai et al, 2015). Studies investigating the side-effects of opioids suggest that in rodents, females suffer from higher rates of opioid-induced hyperalgesia than males (Holtman and Wala, 2005; Juni et al, 2008).…”
Section: Opioid Analgesiasupporting
confidence: 59%
“…Indeed, using a variety of acute and chronic pain assays, researchers have shown that morphine’s median effective dose in female rodents is approximately twice the concentration of the dose needed for males to achieve comparable levels of pain relief (Kepler et al, 1989; Cicero et al, 2002; Ji et al, 2006; Loyd and Murphy, 2006; Loyd et al, 2008; Posillico et al, 2015). Researchers using other opioids have reported similar results (Barrett et al, 2002; Bai et al, 2015). Studies investigating the side-effects of opioids suggest that in rodents, females suffer from higher rates of opioid-induced hyperalgesia than males (Holtman and Wala, 2005; Juni et al, 2008).…”
Section: Opioid Analgesiasupporting
confidence: 59%
“…Since the level of AR receptor expression in TG is comparable between male and female rats (Lee et al, 2013), and that AR is hereby shown to bind to the Oprm1 promoter region in female TG, it is reasonable to assume that the circulating testosterone level in female is not sufficient to elicit MOR induction under inflammatory conditions. Such testosterone dependent regulation of MOR within TG has been demonstrated in a myositis model (Zhang et al, 2014) as well as in a tendon ligation model (Bai et al, 2015). In both models, inflammation- or injury-induced upregulation of MOR in TG is impaired in female and GDX rats and that testosterone replacement in GDX male rats restores the expression of MOR and the efficacy of peripherally administered MOR agonists.…”
Section: Discussionmentioning
confidence: 86%
“…We defined mechanical allodynia as the presence of a nocifensive behavioral response evoked at a mechanical threshold that previously did not evoke a nocifensive response. Changes in nocifensive behavioral responses were evaluated by using previously described methods (3,23,24). To confirm bilateral allodynia, the nocifensive behavior response after unilateral CFA or saline injection into the masseter muscle was measured bilaterally at different time points using a von Frey anesthesiometer (VFA; type 2391, IITC Inc., Woodland Hills, CA, USA) with the tip size of 1.0 mm.…”
Section: Methodsmentioning
confidence: 99%